Review of systemic chemotherapy in unresectable colorectal peritoneal carcinomatosis. Issue 1 (19th February 2021) - Nindra, Udit; Shahnam, Adel; Mahon, Kate L.
Abstract: Colorectal cancer remains the third most common malignancy in Australia with the peritoneum being the second most common metastatic site. Colorectal peritoneal carcinomatosis (CPC) can be treated with cytoreductive surgery and hyperthermic intraperitoneal chemotherapy but this is only limited to a small subset of patients. Those with inoperable disease have a particularly poor prognosis. While the ideal systemic regimen has not been defined, 5‐fluorouracil‐based chemotherapy regimens appear to provide overall and progression free survival benefits. The role of targeted agents such as bevacizumab (vascular endothelial growth factor inhibitor) or cetuximab (epidermal growth factor inhibitor) in the setting of CPC is still evolving. Currently, retrospective analyses have shown promising results for the use of bevacizumab in addition to systemic chemotherapy but similar results have not been seen with cetuximab or panitumumab. However, there is significant heterogeneity in the trial data, lack of prospective randomized controlled trials and demonstrated treatment variability based on age and tumour characteristics. This review summarises the current literature in regard to treatment in the unresectable CPC setting as well as discussing issues with the current data and highlighting the need for further trials.